Tracking everyday change: A guide to process documentation in implementing socio-technical innovation bundles in India - Mukhopadhyay, Prama; Chadha, Deepali; Gartaula, Hom Nath; Puskur, Ranjitha; Goel, Kritika (CGIAR Initiative on Gender Equality, 2024)
Documenting everyday change in development interventions is a complex process. It involves real-time tracking of activities, capturing dynamic processes, and addressing emerging challenges, and enabling iterative improvements. Within the CGIAR Initiative on Gender Equality, we implemented an action research project in West Bengal, India to capture the everyday change of smallholder women livestock farmers as they navigate with the climate vulnerabilities they face in their everyday life. The project strengthens their roles in sustainable, climate-smart agrifood systems through integrated interventions that encompass social, technological, and technical innovations, called socio-technical innovation bundles (STIBs). Our preliminary results illustrate that transparent and inclusive documentation not only enhances accountability but also builds trust, facilitating learning and adaptive management across all stakeholder groups. By enabling equitable decision-making, these practices increase confidence of women farmers and other partners to meaningfully contribute to project outcomes in the long run. This research brief outlines a guide on documenting the process of everyday change while implementing STIBs in a framework of participatory action research.